2002
DOI: 10.1093/jnci/94.7.497
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy and the Risk of Invasive Epithelial Ovarian Cancer in Swedish Women

Abstract: Ever users of ERT and HRTsp but not HRTcp may be at increased risk of EOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
157
4
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(178 citation statements)
references
References 55 publications
12
157
4
5
Order By: Relevance
“…In contrast, several studies published since this metaanalysis have suggested that long-term use of E-alone may increase risk [5,7,15,29,30]. In a cohort study, Lacey et al detected a significantly increased risk of ovarian cancer in women who had used estrogen therapy for 10-19 years (HR=1.8, 95% CI: 1.1-3.0) or more than 20 years (HR=3.2, 95% CI: 1.7-5.7) compared to never users [15].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In contrast, several studies published since this metaanalysis have suggested that long-term use of E-alone may increase risk [5,7,15,29,30]. In a cohort study, Lacey et al detected a significantly increased risk of ovarian cancer in women who had used estrogen therapy for 10-19 years (HR=1.8, 95% CI: 1.1-3.0) or more than 20 years (HR=3.2, 95% CI: 1.7-5.7) compared to never users [15].…”
Section: Discussionmentioning
confidence: 67%
“…Results from studies conducted in the U.S. [5,11,[13][14][15]31,32], Australia [33], Norway [8], Sweden [29], and U.K [7] have been inconclusive regarding the relationship between EP and ovarian cancer. Overall, we detected no associations with EP use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses (Garg et al, 1998;Coughlin et al, 2000) and certain case -control studies (Weiss et al, 1982;Riman et al, 2002) also failed to find a significant trend with duration of use, although some found a positive association (Risch, 1996) or suggested a positive trend (Kaufman et al, 1989;Bosetti et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, unopposed estrogen use has been positively associated with ovarian cancer risk or mortality in several cohort studies (Rodriguez et al, 2001;Lacey et al, 2002Lacey et al, , 2006Folsom et al, 2004). Although estrogen plus progestin use also has been examined in multiple studies (Lacey et al, 2002(Lacey et al, , 2006Riman et al, 2002;Sit et al, 2002), only one cohort study reported a substantial number of cases among long-duration estrogen plus progestin users, finding a significant increased risk of ovarian cancer (Lacey et al, 2006).…”
mentioning
confidence: 99%